Birkat Shalom: Studies in the Bible, Ancient Near Eastern Literature, and Postbiblical Judaism Presented to Shalom M. Paul on the Occasion of His Seventieth Birthday - Ahituv, Shmuel; Amit, Yairah; Artzi, Pinhas; Aster, Shawn Zelig; Avigdor Hurowitz, Victor; Barmash, Pamela; Ben-Dov, Jonathan; Berlin, Adele; Cazelles, Henri; Cogan, Mordechai; Cohen, Chaim; Cohen, Chaim; et al. (Penn State University Press, 2021)
Frontmatter -- Contents -- Shalom Paul: Scholar, Teacher, Friend -- Publications of Shalom M. Paul -- Abbreviations -- Volume 1 -- Part 1 The Bible -- The Torah -- Statut Public et Droit Privé dans la Tôrâh -- Exodus 21:22–25 Revisited: Methodological Considerations -- Three Major Redactors of the Torah -- Nimrod, Son of Cush, King of Mesopotamia, and the Dates of P and J -- A Linguistic Analysis of the Phrase צל משצנחך-צל (Exodus 21:19) and the Homiletic Sense צל משצנחך-צל בזזיך -- Burnt Offering of Head, Peder, and Kidneys -- The Desecration of YHWH’s Name: Its Parameters and Significance -- Alliteration in the Exodus Narrative -- Deuteronomic Concepts of Exile Interpreted in Jeremiah and Ezekiel -- Light in Genesis 1:3— Created or Uncreated: A Question of Priestly Mysticism? -- The Historical Books -- “They Feared God”/“They Did Not Fear God”: On the Use of yéreª Yhwh and yareª ªet Yhwh in 2 Kings 17:24–41 -- The Lament of David over Abner -- Oracle Inquiries in Judges -- King Solomon -- Synchronic and Diachronic Considerations in the DtrH Portrayal of the Demise of Solomon’s Kingdom -- “And the Lord Sent Moses and Aaron” -- The Davidic-Solomonic Empire from the Perspective of Archaeological Bibliology -- The Books of the Prophets -- The Sinai Theophany in the Psalm of Habakkuk -- Jeremiah 3:1–4:2 between Deuteronomy 24 and Matthew 5: Jeremiah’s Exercise in Ethical Criticism -- The Historical Background of the Prophecies of Amos -- Isaiah and the Transition from Prophecy to Apocalyptic -- Engendering Ezekiel: Female Figures Reconsidered -- Zechariah 12:12–14 and Hosea 10:5 in the Light of an Ancient Mourning Practice -- The Ultimate Aim of Israel’s Restoration in Ezekiel -- Is It Good for the Jews? Ambiguity and the Rhetoric of Turning in Isaiah -- The Message of Psalm 114 -- The Writings -- A New Criterion for Identifying “Wisdom Psalms” -- Concepts of Wisdom in the Book of Proverbs -- “The Voice of Yhwh Causes Hinds to Calve” (Psalm 29:9) -- The Influence of Legal Style on the Style of Aphorism The Origin of the Retribution Formula and the Clause loª yinnaqeh ‘He Will Not Go Unpunished’ in the Book of Proverbs -- Part 2 The Bible and the Ancient Near East -- The Mesopotamian Background of the Term אחךימ חימים in the World-Peace Vision of Isaiah 2:2a -- The Lions of Nineveh (Nahum 2:12–14): A Check on Nahum’s Familiarity with Assyria -- New Directions in Modern Biblical Hebrew Lexicography -- Ahab and Archaeology: A Commentary on 1 Kings 16–22 -- Hurrian Ullikummi and Daniel’s “Little Horn” -- Reanalysis in Biblical and Babylonian Poetry -- In Search of Resen (Genesis 10:12): Dur-Sarrukin? -- Deuteronomy 6:6, 9 in the Light of Northwest Semitic Inscriptions -- The Myth of Tammuz in Biblical Narrative -- Volume 2 -- Part 3 The Ancient Near East -- Scribal Initiative in the Clarification and Interpretation of Mesopotamian Law Collections -- Two Aramaic Ostraca from a Tannery in ºÊn Gedî -- A Late Iron Age Hebrew Letter Containing the Word Noqédîm -- Wordplay in the Lamastu Incantations -- “The Ship of the Desert, the Donkey of the Sea”: The Camel in Early Mesopotamia Revisited -- “Secular” Love Songs in Mesopotamian Literature -- A Seated Figurine from Tell eß-Íâfi/Gath: A Philistine Image of El? -- The Deity Addu (Hadad) of Kallassu (near Aleppo) in Two Mari Letters -- Negotiating with Hammu-rapi: A Case Study -- The Love Poem of Rim-Sîn and Nanaya -- On rahaßum I, II, III and on Akkadian rihßum = Hebrew ץצרה -- From Biqºat to KTK: “All Aram” in the Sefîre Inscription in the Light of Amos 1:5 -- Two Become One: A Unique Memorandum of Obligation -- Part 4 Postbiblical, Medieval, and Modern Judaism -- The Place of Genres in Bible Curricula -- The Three-Day Period of Purification before Entering the Temple -- Scribal Interventions in 1QIsaiaha -- The “Plotting Witness” and Beyond: A Continuum in Ancient Near Eastern, Biblical, and Talmudic Law -- Franz Rosenzweig and the Land of Two Rivers -- Rashi and the “Messianic” Psalms -- “The Lovers’ Way”: Cultural Symbiosis in a Medieval Commentary on the Song of Songs -- A Rather Risqué Pun in Jewish Babylonian Aramaic -- The “Voice” of the Narrator and the “Voice” of the Characters in the Bible Commentaries of Yefet ben ºEli -- Codification of Jewish Law in the Dead Sea Scrolls -- Mismarot Lists (4Q322–324c) and “Historical Texts” (4Q322a; 4Q331–4Q333) in Qumran Documents -- Literary Analysis, the So-Called Original Text of Hebrew Scripture, and Textual Evaluation -- Sources for the Astronomy in 1 Enoch 72–82 -- I. O. Lehman, HUC mss 951–981 from Kai Feng, and a Purported Link between China and Yemen -- Philo and Maimonides on the Garden of Eden Narrative -- Indexes